Perancangan produk mainan statis untuk meningkatkan kecerdasan anak - RA.MM Pandansari Kusumo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2018)
Child development starts from inside the mother's womb, and is very dependent on the family environment and the surrounding environment, including food intake, attention and love by parents, playground, playmates, including the type of toys they play. Basically a child will be happy and playful when the toy can be fun for him. However, as a parent or a more mature person, they must also be selective in choosing the toy. Today more and more children stick to gadget, so they rarely play with toys that should be played for children their age. Actually there are a lot of variety of children's toys around us, ranging from dolls, trains, puzzles, cars, and so on. Even if you remember from time immemorial people also know traditional toys such as marbles, ‘dakon’, ‘sumbar suru’, ‘bekel’ balls, slingshots, and many others. In this study, the researcher took care in order to restore the habits of children in playing, through the development of dakon product design for revitalization.. The goal is to introduce dakon games to children in a more fresh form. The dakon product made is intended for children aged 3-5 years. Key words: child growth, toy products, dakon